Method for realizing high-reliability interconnection of carbon nanotube fiber and metal through brazing
By depositing nickel or copper plating on the surface of carbon nanotube fibers and combining with the rapid spray deionized water cooling process, the interconnection problem between carbon nanotube fibers and metals is solved under low temperature conditions, high-reliability welding is achieved, and service reliability and thermal shock resistance are improved.
Patent Information
- Application Number
- CN202311131153.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The prior art is difficult to achieve reliable interconnection between carbon nanotube fibers and metals under low temperature conditions, and the wettability of traditional solder and carbon nanotube fibers is poor, resulting in poor welding and affecting service reliability.
Highly reliable interconnection of carbon nanotube fibers and metals is achieved by depositing nickel or copper plating at the to-be-welded part of carbon nanotube fibers and utilizing traditional tin-based brazing materials, combined with a rapid spray deionized water cooling process.
It improves the bonding strength and wettability of the interface between carbon nanotube fibers and solder, reduces the difference in thermal expansion coefficient, significantly improves the service reliability of welding, and maintains excellent resistance to cold and cold impact in extreme environments.
Smart Images

Figure CN119549822A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of reliable interconnection between carbon nanotube fibers and metals, and in particular to a method for realizing high-reliability interconnection between carbon nanotube fibers and metals by brazing. Background Art
[0002] Lightweight, high-strength, and high-conductivity carbon nanotube fibers are one of the most competitive candidates for the next generation of new conductor materials. Carbon nanotube fibers have the characteristics of corrosion resistance, high flexibility, high tensile strength, weak skin effect at high frequencies, and light weight. As a new type of conductor material, they have excellent weight reduction effects, and therefore have great application prospects in many fields such as aerospace, national defense, and civil use. However, due to the chemical inertness of carbon nanotubes themselves, they do not react with metals under medium and low temperature conditions, and have poor wettability with traditional solders. Therefore, the interconnection between carbon nanotubes and metal electrodes in functional components faces the problem of "unable to weld" and "unsoliciting", which seriously restricts the application of carbon nanotube fibers as circuit conductors. Therefore, achieving reliable electrical interconnection between carbon nanotube fibers and metal electrodes is the key to promoting their practical application. At present, representative works on realizing interconnection between carbon nanotube fibers and metals include: (1) crescent-shaped local electrodeposition interconnection (Literature 1: Zhao C., Luo Z., Ao S., et al. Carbon, 2017, 125, 269-279); (2) ultrasonic welding interconnection (Literature 2: Peng L., Jiang K., Liu M., et al. Appl. Phys. Lett. 2003, 82, 1763-1765); (3) mechanical crimping interconnection (Literature 3: Schauerman C. M., Alvarenga J., Staub J., et al. Adv. Eng. Mater. 2015, 17, 76-83.); (4) conductive adhesive interconnection (Literature 4: Kim EJ, Luan VH, Tien HN, et al. J. Mater. Chem. 2012, 22, 8649-8653). (5) Traditional brazing interconnection (Reference 5: Burda M., Lekawa-Raus A., Gruszczyk A., et al. ACS Nano 2015, 9(8), 8099-8107). In order to be compatible with the production processes of integrated circuits and microelectronic devices, it is necessary to develop a high-reliability interconnection process with a low soldering temperature. Among the above interconnection methods, traditional brazing has low cost, simple process, and strong operability at relatively low temperatures, so it has great application potential in the interconnection of carbon nanotube fibers.
[0003] However, the current use of brazing to achieve reliable interconnection between carbon nanotube fibers and metals still faces great challenges: (1) The wettability of carbon nanotube fibers and brazing solder is poor, resulting in low service reliability due to "poor welding"; (2) The density of carbon nanotube fibers is between 1.1 and 2.0 g / cm3, which is much lower than the density of tin-based solder (6.5 to 8.8 g / cm3). Therefore, carbon nanotube fibers tend to float on the surface of molten liquid solder, resulting in "unable to weld" due to the separation of the two; (3) Although adding a high content of transition metal elements to the traditional solder formula can significantly improve the wettability of carbon nanotube fibers and solder alloys (Reference 5: Burda M., Lekawa-Raus A., Gruszczyk A., et al. ACS Nano 2015, 9(8), 8099-8107), but its welding temperature is relatively high (350℃), which causes a large number of large-sized brittle intermetallic compounds to exist in the solder joint, resulting in a significant reduction in the service reliability of the solder joint; (4) There is a large difference between the thermal expansion coefficient of the carbon nanotube fiber and the thermal expansion coefficient of the solder alloy. In a service environment with large temperature changes, residual stress is easily generated at the interface of the welded workpiece, thereby causing crack initiation at the interface; (5) The bonding strength of the heterogeneous interface between the carbon nanotube fiber and the solder is low, resulting in a low service life of the solder.
[0004] In summary, the main problem currently faced is: how to be compatible with traditional brazing micro-interconnection technology and process without changing the classic formula components of the solder alloy, and solve the difficult problems of "not being able to weld" and "not being welded firmly" during the brazing interconnection process between carbon nanotube fibers and metal substrates, and develop a carbon nanotube fiber-metal welding interconnection method with simple process, low cost and high service reliability. Summary of the invention
[0005] The purpose of the present invention is to provide a method for highly reliable interconnection between carbon nanotube fibers and metals by brazing, which has a simple process, low cost and high service reliability, solves the problem of "not being able to weld" and "not being able to weld firmly" between carbon nanotube fibers and metals, and realizes reliable interconnection between carbon nanotube fibers and metals.
[0006] The technical solution of the present invention is:
[0007] A method for achieving high-reliability interconnection between carbon nanotube fibers and metals by brazing, wherein conventional tin-based brazing solder is selected, a metal substrate to be welded is heated to a predetermined temperature in air using a flat hot plate, and when the solder ball melts, it wets and spreads on the surface of the substrate, and the pre-treated carbon nanotube fiber to be welded is placed on the surface of the molten liquid solder alloy, and when the solder alloy on the surface of the carbon nanotube fiber melts, it is rapidly solidified, thereby achieving brazing interconnection between the carbon nanotube fiber and the metal;
[0008] Among them, the pretreatment process of the part to be welded of the carbon nanotube fiber is: a nickel plating layer or a copper plating layer is deposited on the part to be welded of the carbon nanotube fiber by an electroplating method, a solder alloy layer is coated on the part to be welded of the carbon nanotube fiber by a mechanical crimping method, and after folding, mechanical pressure is applied to realize a carbon nanotube fiber to be welded sample with mechanical interconnection strength.
[0009] The method for achieving high-reliability interconnection between carbon nanotube fibers and metals by soldering adopts a commercially available classic solder component as the solder alloy, including tin-lead solder, tin-copper solder, tin-silver solder or tin-bismuth solder.
[0010] In the method for realizing high-reliability interconnection between carbon nanotube fibers and metals by brazing, the contact time between the carbon nanotube fibers and the molten liquid solder alloy is relatively short, usually between 3 and 10 seconds.
[0011] In the method for realizing high-reliability interconnection between carbon nanotube fibers and metals by brazing, the thickness of the nickel plating layer or the copper plating layer is 0.1 to 0.7 μm, and the length is 1 to 2 cm.
[0012] The method for achieving high-reliability interconnection between carbon nanotube fibers and metals by brazing prevents separation of the carbon nanotube fibers and the liquid solder alloy by rapidly spraying deionized water to reduce the temperature of the molten liquid solder alloy to below the melting point, thereby achieving rapid solidification.
[0013] In the method for realizing high-reliability interconnection between carbon nanotube fibers and metals by brazing, the deionized water spraying time is 2 to 5 seconds.
[0014] The method for achieving high-reliability interconnection between carbon nanotube fibers and metals by brazing comprises pretreating the parts of the carbon nanotube fibers to be welded, modifying the surfaces of the parts of the carbon nanotube fibers to be welded to prepare interconnection solder joints, and improving the bonding strength, wettability and thermal expansion coefficient difference between the carbon nanotube fibers and the solder interface.
[0015] The method for achieving high-reliability interconnection between carbon nanotube fibers and metals by brazing, wherein the interconnection solder joints prepared by modifying the parts of the carbon nanotube fibers to be welded have excellent resistance to thermal shock in thermal shock cycle tests in extreme environments, when the temperature is rapidly reduced from 150°C to -196°C in 2 to 5s, the resistance change rate is less than 30% after 450 cycles of thermal shock tests.
[0016] The design concept of the present invention is:
[0017] The present invention proposes to use lightweight, high-strength, and highly conductive carbon nanotube fibers as a new type of conductor. First, the surface of the carbon nanotube fibers to be welded is modified to improve the bonding strength, wettability, and thermal expansion coefficient difference between the carbon nanotube fibers and the solder interface. At the same time, a rapid solidification welding process is developed to achieve controllable preparation of welded interconnections between the carbon nanotube fibers and the metal matrix through the rapid solidification method, thereby achieving reliable interconnection between the carbon nanotube fibers and the metal without changing the traditional classical solder composition.
[0018] The solder alloy used in the present invention is a commercialized classic solder component, and there is no need to add transition metal components to the traditional solder alloy. The brazing temperature does not exceed 300°C, which ensures the service reliability of the solder alloy itself. At the same time, good wetting between the solder alloy and the carbon nanotube fiber is achieved, and the bonding strength of the carbon nanotube fiber / solder heterogeneous interface is improved, thereby improving the interconnection reliability between the carbon nanotube fiber and the metal matrix. In addition, the present invention uses an electroplating method to deposit a nickel plating layer or a copper plating layer on the to-be-welded portion of the carbon nanotube fiber. The nickel plating layer or the copper plating layer is used to improve the bonding strength, wettability and thermal expansion coefficient difference between the carbon nanotube fiber and the solder interface.
[0019] The advantages and beneficial effects of the present invention are:
[0020] (1) The present invention uses a tin-based alloy with a traditional classical component ratio as solder, and develops a rapid cooling welding process by spraying deionized water. During the welding process, deionized water is sprayed on the molten solder to achieve rapid cooling and solidification, thereby solving the problem of "not being able to weld" carbon nanotube fibers and metals due to the large density difference.
[0021] (2) The present invention introduces a buffer layer on the surface of the carbon nanotube fiber to be welded, thereby significantly improving the wettability of the solder and the carbon nanotube fiber and reducing the difference in thermal expansion coefficients, thereby improving the bonding strength of the interface between the carbon nanotube fiber and the solder alloy. By introducing a nickel plating layer or a copper plating layer with high bonding energy as an intermediate buffer layer on the carbon nanotube fiber to be welded, the problem of "poor welding" between the carbon nanotube fiber and the metal is solved.
[0022] (3) The present invention utilizes a simple and effective method to get rid of the constraint of adding transition metal elements into the tin-based solder alloy to obtain a "carbon-based special" solder. Traditional classic brands of tin-based solder can be used, and it is highly compatible with traditional brazing microelectronic packaging technology, making it easy to apply and promote.
[0023] (4) The carbon nanotube fiber-metal interconnects prepared by the present invention have high service reliability, laying a foundation for promoting the electrical application of carbon nanotube fibers as lightweight, high-strength, and high-conductivity transmission lines. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) SEM image of the surface of the carbon nanotube fiber to be welded coated with nickel. (b) Backscattered electron morphology of the radial cross section of the carbon nanotube fiber coated with nickel.
[0025] Figure 2 (a) SEM image of the carbon nanotube fiber / nickel coating / solder alloy interface. (b) Linear scan of nickel elements from the fiber to the inside of the solder, with the horizontal axis representing position (μm) and the vertical axis representing relative intensity (counts).
[0026] Figure 3 .SEM image of the carbon nanotube fiber / nickel coating / solder interface after 450 thermal shock tests.
[0027] Figure 4 (a) SEM image of nickel-coated carbon nanotube composite fiber fabric. (b) Contact angle of Sn-37Pb solder ball heated and liquefied at 250℃ on the surface of nickel-coated carbon nanotube fiber fabric.
[0028] Figure 5 .Scanning electron micrograph of the copper coating on the surface of carbon nanotube fibers.
[0029] Figure 6 .SEM image of the carbon nanotube fiber / copper coating / solder interface after 450 thermal shock tests.
[0030] Figure 7 .SEM image of the carbon nanotube fiber / solder interface without buffer layer modification after 450 thermal shock tests.
[0031] Figure 8 (a) SEM image of carbon nanotube fiber fabric without buffer layer modification. (b) Contact angle of Sn-37Pb solder ball heated and liquefied at 250℃ on the surface of carbon nanotube fiber fabric. DETAILED DESCRIPTION
[0032] In the specific implementation process, the present invention proposes a method for achieving high-reliability interconnection between carbon nanotube fibers and metals through brazing, which uses electrodeposition technology to introduce a metal buffer layer on the surface of the carbon nanotube fibers to be welded, uses tin-gold alloy as solder, and uses traditional brazing methods to achieve interconnection between the carbon nanotube fibers and metals.
[0033] First, a certain thickness of metal layer is deposited on the part of the carbon nanotube fiber to be welded by electroplating process. The purpose is that the presence of the metal buffer layer can improve the bonding strength of the carbon nanotube fiber / solder interface and reduce the residual stress generated by the carbon nanotube fiber and the solder alloy in the service environment with large temperature changes. Then, tin-based solder is used to achieve brazing interconnection between the carbon nanotube fiber and the metal by using a rapid cooling process.
[0034] The preparation steps of this method are as follows:
[0035] (1) Pretreatment of carbon nanotube fibers:
[0036] The carbon nanotube fiber is wound on a stainless steel square frame, and both ends of the fiber are adhered and fixed to the surface of the stainless steel frame with conductive carbon glue. A metal coating (nickel coating) is deposited on the welding position of the carbon nanotube fiber using a two-electrode method.
[0037] (2) Brazing process:
[0038] The solder balls are placed on the surface of the polished metal substrate, and the metal substrate and the solder balls are heated using a flat hot plate. Under the action of the rosin-based flux, the molten solder alloy wets and spreads on the surface of the metal substrate, thereby prefabricating a solder buffer layer on the surface of the copper substrate. The modified carbon nanotube fibers coated with the solder alloy are placed on the surface of the molten solder alloy. When the molten liquid solder alloy fully wets and immerses the carbon nanotube fibers, deionized water is sprayed to rapidly solidify the solder alloy, thereby forming a carbon nanotube fiber-metal interconnect conductor.
[0039] The present invention is further described in detail below through examples and drawings.
[0040] Example 1
[0041] In this embodiment, the surface of the carbon nanotube fiber is modified by the above step (1), and the length of the nickel plating layer is controlled by controlling the depth of the carbon nanotube fiber to be welded in the electrolyte, and the thickness of the nickel plating layer is controlled by the electroplating time. The formula of the nickel electroplating solution is: 50g / L nickel sulfate, 10g / L nickel chloride, 80g / L sodium citrate, and the balance is water; the deposition time is 30s, the temperature is 65℃, and the current density is 1-1.5A / dm 2 .like Figure 1 As shown in a, the surface of the carbon nanotube fiber to be welded is coated with a nickel coating. The scanning electron microscope image shows that the nickel coating is uniformly coated on the surface of the carbon nanotube fiber, and its thickness is 0.5 to 0.7 μm ( Figure 1 b), length is 1 to 2 cm.
[0042] The above step (2) is used to place the Sn-37Pb eutectic solder ball on the surface of the polished copper substrate, and the solder ball is heated to 250°C to melt and wet and spread on the surface of the copper substrate. A strong bond is achieved at the solder / copper interface by forming an intermetallic compound. The nickel-plated carbon nanotube fiber to be welded is coated again with a solder alloy, and then placed on the surface of the molten solder on the copper substrate. When the solder fully infiltrates the carbon nanotube fiber, deionized water is quickly sprayed for 3 seconds to make the temperature of the molten liquid solder alloy drop sharply to below the melting point, thereby achieving rapid solidification of the solder and welding and interconnection of the carbon nanotube fiber and the copper substrate. Figure 2 As shown in a, the microstructure of the carbon nanotube fiber / nickel / solder interface shows that the nickel coating is well bonded to the carbon nanotube fiber and solder. Figure 2 As shown in b, the linear scanning energy spectrum of the nickel element at the interface of carbon nanotube fiber / nickel / solder also proves that the nickel plating exists at the interface of the solder joint.
[0043] The carbon nanotube fiber-copper solder interconnect was subjected to 450 thermal shock cycle tests (the sample was rapidly cooled from 150°C to -196°C within 5-10 seconds), and its resistance change rate was measured to be 29.8%. Figure 3 As shown in the figure, the scanning electron microscope photo of the carbon nanotube fiber / nickel coating / solder interface shows that only one micro crack appears at the carbon nanotube fiber / solder interface modified by nickel coating, indicating that the carbon nanotube fiber-copper solder interconnect modified by nickel coating has relatively high service reliability in extreme environments and has great application potential. In addition, Figure 4 As shown in Figure a, a carbon nanotube fiber modified with a nickel plating layer as an intermediate buffer layer is made into a fabric, a Sn-37Pb solder ball with a diameter of 760μm is placed on the surface of the carbon nanotube fiber fabric modified with the nickel buffer layer, and the fabric and the Sn-37Pb solder ball are heated at 250℃ using a flat hot stage. Then, the contact angle of the solder after wetting and spreading on the fabric surface is measured using a contact angle meter, and the contact angle is about 0°( Figure 4 b). The results show that the wettability between the liquid solder alloy and the carbon nanotube fibers is good after the nickel buffer layer is modified.
[0044] Embodiment 2:
[0045] In this embodiment, step (1) is the same as step (1) of the embodiment. The formula composition of the copper electroplating solution is: 180g / L copper sulfate, 0.56mol / L sulfuric acid, 0.001mol / L hydrochloric acid, and the balance is water; the deposition time is 30s, and the current density is 1-1.5A / dm 2 .like Figure 5 As shown, the scanning electron microscope image of the copper coating on the surface of the carbon nanotube fiber shows that the copper coating is evenly coated on the surface of the carbon nanotube fiber, and the coating has a thickness of 0.5 to 0.7 μm and a length of 1 to 2 cm.
[0046] Step (2) is the same as step (2) in the embodiment. The carbon nanotube fiber-copper soldered interconnect modified by copper plating was subjected to 450 thermal shock tests (the sample was rapidly cooled from 150°C to -196°C within 5-10s), and its resistance change rate was measured to be 33.2%. Figure 6 As shown, the scanning electron microscope photograph of the carbon nanotube fiber / copper plating / solder interface indicates that the introduction of the copper buffer layer can enable the carbon nanotube fiber / solder interface to maintain excellent thermal shock resistance, thereby significantly improving the service reliability of the carbon nanotube fiber-copper soldered interconnection in extreme environments.
[0047] Comparative Example 1: Brazing interconnection between carbon nanotube fibers without buffer layer and copper
[0048] This comparative example does not include step (1) of Example 1, and the welding process is the same as step (2) of Example 1, that is, the carbon nanotube fiber replaces the nickel-coated carbon nanotube fiber in Example (1), and the other processes are exactly the same. The results show that the carbon nanotube fiber without buffer layer modification can also achieve welding interconnection between the carbon nanotube fiber and the copper substrate through step (2) of Example.
[0049] The carbon nanotube fiber-copper soldered interconnect without metal buffer layer modification was subjected to 450 thermal shock tests (the sample was rapidly cooled from 150°C to -196°C within 5-10s), and its resistance change rate was measured to be 235.3%. Figure 7 As shown in the figure, the scanning electron microscope photo of the carbon nanotube fiber / solder interface shows that when there is no buffer layer, large-sized holes appear at the carbon nanotube fiber / solder alloy interface, which seriously weakens the thermal shock resistance of the carbon nanotube fiber-copper interconnect, thereby reducing its service reliability in extreme thermal environments. Figure 8 As shown in Figure a, carbon nanotube fibers modified without a metal buffer layer are made into fabrics, Sn-37Pb solder balls with a diameter of 760 μm are placed on the surface of the carbon nanotube fiber fabric, and the fabric and Sn-37Pb solder balls are heated at 250°C using a flat hot plate. The contact angle of the solder on the fabric surface after wetting and spreading is about 107° ( Figure 8 b). The results show that when there is no buffer layer, the liquid solder alloy and the carbon nanotube fibers are in a lyophobic state, that is, the wettability is poor.
[0050] Comparative Example 2: Rapid Solidification Process without Deionized Water Spraying
[0051] Step (1) of this comparative example is exactly the same as step (1) of the embodiment. Step (2) is exactly the same as step (2) of the embodiment, except that the rapid solidification process of spraying deionized water is missing. It is found that when the rapid solidification process is missing in the welding process, the carbon nanotube fibers float on the surface of the liquid solder due to their low density, and ultimately the welding interconnection between the carbon nanotube fibers and the copper substrate cannot be achieved.
[0052] The above embodiments and comparative examples illustrate that the present invention has developed a rapid cooling welding process by spraying deionized water, which solves the problem of "not being able to weld" the carbon nanotube fiber to the metal matrix, and solves the problem of "not being able to weld firmly" by introducing a metal buffer layer technology (nickel and copper) at the welding position. Although the present invention has been described in detail above with general descriptions and specific implementation schemes, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention are within the scope of protection claimed by the present invention.
Claims
1. A method for achieving high-reliability interconnection between carbon nanotube fibers and metal by brazing, characterized in that: A conventional tin-based brazing solder is used, and a flat hot plate is used to heat the metal substrate to be welded to a predetermined temperature in the air. When the solder ball melts, it wets and spreads on the surface of the substrate. The pre-treated carbon nanotube fiber to be welded is placed on the surface of the molten liquid solder alloy. When the solder alloy on the surface of the carbon nanotube fiber melts, it is quickly solidified, thereby achieving brazing interconnection between the carbon nanotube fiber and the metal. Among them, the pretreatment process of the part to be welded of the carbon nanotube fiber is: a nickel plating layer or a copper plating layer is deposited on the part to be welded of the carbon nanotube fiber by an electroplating method, a solder alloy layer is coated on the part to be welded of the carbon nanotube fiber by a mechanical crimping method, and after folding, mechanical pressure is applied to realize a carbon nanotube fiber to be welded sample with mechanical interconnection strength.
2. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 1, characterized in that: The solder alloys used are commercially available classical solder compositions, including tin-lead solder, tin-copper solder, tin-silver solder or tin-bismuth solder.
3. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 1, characterized in that: The contact time between the carbon nanotube fiber and the molten liquid solder alloy is relatively short, usually between 3 and 10 seconds.
4. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 1, characterized in that: The thickness of the nickel plating layer or the copper plating layer is 0.1 to 0.7 μm, and the length is 1 to 2 cm.
5. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 1, characterized in that: In order to prevent the carbon nanotube fibers from being separated from the liquid solder alloy, the temperature of the molten liquid solder alloy is rapidly dropped to below the melting point by spraying deionized water, thereby achieving rapid solidification.
6. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 5, characterized in that: The deionized water spraying time is 2 to 5 seconds.
7. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 1, characterized in that: By pretreating the to-be-welded portion of the carbon nanotube fiber, the to-be-welded portion of the carbon nanotube fiber is surface-modified to prepare interconnection solder joints, thereby improving the bonding strength, wettability and thermal expansion coefficient difference between the carbon nanotube fiber and the solder interface.
8. The method for realizing high-reliability interconnection between carbon nanotube fibers and metal by brazing according to claim 7, characterized in that: The interconnection solder joints prepared by modifying the parts to be welded of the carbon nanotube fibers have excellent resistance to thermal shock in extreme environment thermal shock cycle tests. When the temperature drops rapidly from 150°C to -196°C in 2 to 5 seconds, the resistance change rate is less than 30% after 450 cycles of thermal shock tests.
Citation Information
Patent Citations
Method for connecting carbon nanotube and metal with electric resistance welding
CN102363240A
Method for manufacturing carbon nano tube flexible micro-bumps through transfer method
CN103367185A
Synthesis method of carbon nanotube array-based thermal interface material capable of being independently used
CN116408505A
Method of brazing carbon nanotube to base material
JP2005074472A
Brazing joining method of CNT assemblies on substrates using an at least ternary brazing alloy; corresponding brazing material and device comprising such assembly
US20160243636A1
Cited By
Carbon nanotube fiber bundle-metal wire connecting method suitable for space electric propulsion thermal control system
CN121468130A